Maternal origin of Medjimurje horse - Cubric-Curik, Vlatka; Frkonja, Anamarija; Kostelic, Antun; Belcic, Marijan; Bokor, Árpád; Druml, Thomas; Curik, Ino (Acta Agraria Kaposváriensis, 2010)
Maternal origin of highly endangered population of Medjimurje horse was analysed with intention to establish maternal lineages, to characterise its position among other horse breeds, to compare Croatian and Hungarian subpopulations and to compare Medjimurje horse with related breeds. To achieve those goals we sequenced fragment of mitochondrial control region (mtDNA D-loop) of 58 Medjimurje horses (27 from Croatian and 24 from Hungarian sub-population) and 7 Norikers from Austria (Carinthia region). We also analysed additional 95 sequences taken from the GeneBank database, representing large number of breeds and representative haplotypes, with particular stress on Arab Horse (17) and Renish German Draft Horse (24). The analyses have shown that out of 51 MH sequences there were 19 different maternal lineages (haplotypes). Out of 153 analysed sequences, nine haplotypes were unique for MH (six for MH-CRO and three for MH-HUN). It is interesting that among those unique haplotypes one was characteristic for nine MH-CRO horses and one for five MH-HUN horses. The phylogenetic analysis has illustrated that, although, maternal lineages of MH horse are present over distinct phylogenetic clusters there is some tendency of grouping around specific haplotypes and the similar pattern was noted between haplotypes of two MH subpopulations. Here, we have not found strong reasons why not to make common breeding program for MH. However, we should be aware that mtDNA analysis reflects remote origin and before proceeding with practical conservation decisions it would be necessary to analyse those two subpopulations based on microsatellite or SNP polymorphism.